2019
DOI: 10.1002/aenm.201901892
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Conductive Hybrid Architecture of Metal–Organic Framework Nanowire Array on Polypyrrole Membrane for All‐Solid‐State Flexible Supercapacitors

Abstract: Metal–organic frameworks (MOFs) with intrinsically porous structures are promising candidates for energy storage, however, their low electrical conductivity limits their electrochemical energy storage applications. Herein, the hybrid architecture of intrinsically conductive Cu‐MOF nanowire arrays on self‐supported polypyrrole (PPy) membrane is reported for integrated flexible supercapacitor (SC) electrodes without any inactive additives, binders, or substrates involved. The conductive Cu‐MOFs nanowire arrays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 56 publications
2
160
0
Order By: Relevance
“…6G). 2,18,[53][54][55][56][57][58][59][60][61] The highest volumetric energy density was achieved 2.0 mW h cm À3 at a 31.65 mW cm À3 power density (Fig. S23B †).…”
Section: Resultsmentioning
confidence: 98%
“…6G). 2,18,[53][54][55][56][57][58][59][60][61] The highest volumetric energy density was achieved 2.0 mW h cm À3 at a 31.65 mW cm À3 power density (Fig. S23B †).…”
Section: Resultsmentioning
confidence: 98%
“…hibited ah ighe nergyd ensity of 76.7 mWhcm À2 at al ow power density of 2mWcm À2 ,a nd the energy density still remained 42.3 mWhcm À2 at ah igh powerd ensity of 25 mW cm À2 ,w hich correspond to volumetric energy densities (E V )o f1 2a nd 6.6 mW hcm À3 at volumetric powerd ensities (P V ) of 0.31 and 3.9 Wcm À3 ,r espectively.F rom Figure7e, it was observed that the flexible supercapacitorm anufactured with LNF-0.1 electrodes could provideb etter electrochemical performance than those flexible supercapacitors reported previously,s uch as graphene/polypyrrole//graphene/polypyrrole (22.9 mWhcm À2 at 0.56 mW cm À2 ), [20] Ni-Co oxide@MnO 2 //AC (52 mWhcm À2 at 17.3 mW cm À2 ), [21] Cu(OH) 2 /CPCC//AC/CC (49 mWhcm À2 at 0.6 mW cm À2 ), [22] NiO@MnO 2 //Fe 2 O 3 (9.62 mWhcm À2 at 28.9mWcm À2 ), [23] Cu-CAT-NWAs/PPy//Cu-CAT-NWAs/PPy (22.4 mWhcm À2 at 1.1 mW cm À2 ), [24] MoS 2 /MnS/GR// MoS 2 /MnS/GR (7 mWhcm À2 at 49.9 mWcm À2 ), [25] Mn 3 O 4 /Gas// CNHs/Gas (14.7 mWhcm À2 at 14.1 mW cm À2 ), [26] and FPCSLP 54 // FPCSLP 54 (72.5 mWhcm À2 at 250 mWcm À2 ). [27] Moreover,tocompare the performance based on the mass of the electrodes, we calculated the energy density (E m in Whkg À1 )a nd power density (P m in Wkg À1 )o ft he flexible device according to the mass of active material( FigureS10, Supporting Information).…”
Section: Electrochemical Performanceo Fflexible Devicementioning
confidence: 99%
“…22,23 Thus, combining PPy of high conductivity with MOFs is expected to signicantly facilitate the electron transfer, and this strategy has been developed in the fabrication of composite combining MOF with PPy as electrode materials for supercapacitors. [24][25][26][27][28] For example, Liu et al 24 integrated ZIF-67 and PPy through electrochemical deposition technology, and the resulting composite was employed as electrode material which exhibited excellent electrocapacitive performance. To the best of our knowledge, owerlike Ni-MOF/PPy composite as electrode material for supercapacitor has never been reported before.…”
Section: Introductionmentioning
confidence: 99%